Accommodating the Role of Central Axis Lecturers through the Total Institutional Method in Higher Education - Rafdi, M. A. (LPPM Undiksha, 2021)
The tendency of total institutions is marked through starting from the stages and processes of formation to the birth of the BP3K, which these stages and processes include Compertmentalization The research method used is descriptive method. This study aims to explore the problem to produce a holistic description of the problem. From the research results that they are termed the middle axis lecturer. then they are grouped at once combined into a container. A container that is in accordance with their characteristics and character is a manifestation with a tendency towards total institutions. the manifestation of the tendency of the total institution to be named BP3K, namely the Field of Curriculum Development and Supervision, Resocialization, Isolation, very binding rules, tight control, the role of centralized regulator / coach. BP3K activities in the form of studies and training as well as regeneration of member resources in the field of functional competencies in the realm of Tri Dharma Perguruan Tinggi. The total institutional element that contributes the most to the benefits and impacts of BP3K when compared to other elements is the element of isolation and the strength of the supervisor. the implication of the research results, that through BP3K is to make the College as the organizer of basic character training for lecturers of universities, information and appreciation for two tutors from BP3K as tutorial implementers Basic Characteristics BP3K is also used as an accreditation consultant as well as a training center for various achievements and expertise for the College.